From Data to Predictions and Decisions: Enabling Evidence-Based Healthcare - Horvitz, Eric (Computing Community Consortium, 2010)
We stand at the brink of a revolution in data-centric healthcare, made possible by advances in computer science. Such a revolution promises to deliver true evidence-based medicine that can enhance the quality of healthcare while cutting costs, and, more generally, enable physicians and patients to make the best decisions with realistically bounded healthcare resources. Enabling evidence-based healthcare will require investments in translating key methods and insights into working systems, as well as for advances in core computer science research and engineering to address key conceptual and engineering bottlenecks. We review directions and opportunities on the path to evidence-based healthcare.
Data Analytic Series